Associated factors to the perception of clinical coordination in the Catalan national health system. (13th November 2019) - Esteve Matalí, L; Vargas, I; Sánchez, E; Cots, F; Plaja, P; Avecilla, À; Ramon, I; Medarde, E; Colomés, L; Vázquez for GAIA, M L
Abstract: Background: Clinical coordination across levels of care is a priority for health systems. The aim is to analyse the factors associated to a high perception of clinical coordination of primary (PC) and secondary care (SC) doctors of the Catalan national health system (NHS). Methods: Cross-sectional study based on the self-administered online questionnaire COORDENA-CAT. Data collection: October-December 2017. Study population: PC and SC (acute and long term) doctors of the public Catalan NHS that had been working for at least one year in the organization, had direct contact with patients and related with doctors of the other level of care. The participation rate was 20.5%, with a sample of 3308 doctors. Outcome variable: perception of clinical coordination across levels of care. Explanatory variables: socio-demographic, employment characteristics, attitude towards work, type of area (according to type of hospital and managing entity), interactional factors, organizational factors and knowledge of existing coordination mechanisms. Stratification variable: level of care. Descriptive and multivariate analysis by logistic regression. Results: Only 32.13% of PC doctors and 35.72% of SC doctors found that patient care was coordinated across care levels within their area. In both levels of care, knowing the doctor of the other level; finding that their practice influences the other care level; finding that the organization's management facilitates coordination; working in an area where the same entity manages SC and majority of PC and to hold joint clinical case conferences are factors positively associated to a high perception of clinical coordination. Besides, there are other positively associated factors exclusive for each level of care. Conclusions: Several common interactional and organizational factors are positively associated to a high perception of care coordination. Introducing policies to enhance such factors can foster care coordination in the Catalan NHS. Key messages: This study found out factors associated to clinical coordination across care levels in each level. It helps to develop specific coordination policies by level of care to address those factors.